2022
DOI: 10.1152/ajpendo.00122.2022
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-induced glucagon secretion and glucagon-induced enhancement of amino acid catabolism are not influenced by ambient glucose levels in mice

Abstract: Amino acids stimulate the secretion of glucagon, and glucagon receptor signaling regulates amino acid catabolism via ureagenesis, together constituting the liver-alpha cell axis. Impairment of the liver-alpha cell axis is observed in metabolic diseases such as diabetes. It is, however, unknown whether glucose affects the liver-alpha cell axis. We investigated the role of glucose on the liver-alpha cell axis in vivo and ex vivo. The isolated perfused mouse pancreas was used to evaluate the direct effect of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…5 A ). The concurrent rise in glucose and insulin is not unique to our study as also others have reported that amino acid injection in mice results in increased glucose levels ( 27 , 28 ). Whether this is potentially due to increased glucagon output from the islets requires further study.…”
Section: Discussionsupporting
confidence: 58%
“…5 A ). The concurrent rise in glucose and insulin is not unique to our study as also others have reported that amino acid injection in mice results in increased glucose levels ( 27 , 28 ). Whether this is potentially due to increased glucagon output from the islets requires further study.…”
Section: Discussionsupporting
confidence: 58%
“…Livers from C57bl/6JRj male and female mice, 10–12 weeks of age, were perfused to investigate any direct effects of glucagon on hepatic lipolysis. Detailed description of the liver perfusion setup including the surgery can be found in [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In either liver or kidney tissue, the groups fed fortified feed led to a restored activity which was a result of Theobroma cacao protection. Urea is a waste product from the amino acid catabolism [61] while creatinine is the by-product of creatine catabolism [62] . The concentration of these products in the serum is regulated by the kidney; hence compromise in its functional status will lead to an increase in the serum.…”
Section: Discussionmentioning
confidence: 99%